(untitled) (Global Journal of Science Frontier Research, 2015)
Onion (Allium cepa L.) is an important vegetable crop for small and commercial growers in Ethiopia where it is produced for both the local and export markets. But loss can be as high as 66% during storage due to loss in bulb fresh mass and sprouting. A study was therefore, conducted with the objective of optimizing curing and topping time for maximum bulb and storage life of onion quality and maximum days of storage on Onion cv. Bombay Red, at Melkassa Agricultural Research Center, Ethiopia, from January to May 2012. Bulbs were cured under shade for 0, 5, 10 and 15 days, respectively. The tops removed immediately, or removed 5, 10 or 15 days after curing or not at all. The experiment was laid out as a RCBD factorial(4x5x7 curing, topping, storage time respectively) and each treatment combination replicated three times. Data were collected with 15 days interval up to 90 days after curing. Data collected included spouted and rotted bulb percentage, bulb total soluble solids (TSS), bulb dry matter, and bulb fresh mass total loss and bulb color.